Analysis and validation of transient thermal model for automobile cabin. (25th July 2017) - Wu, Jianghong; Jiang, Feng; Song, Hang; Liu, Chaopeng; Lu, Biwang
Highlights: Fast calculation dynamical thermal load model based on response factor method. Accurate validation with experimental tests in real outdoor conditions. Analysis of effects of thermophysical parameters, radiation parameters and driving parameters on thermal load. Cutting down thermal conductivity of envelopes will be the most effective method among thermophysical parameters. Abstract: As automobile cabin thermal environment is complex and continually varies during its travel on road, a dynamical thermal load model based on response factor method has been presented in this paper. To shorten the calculating time, a fast-response thermal load calculation scheme has been proposed which has optimized iterative error, and the calculating time can be finally reduced to 0.95 s when time step is 50 s. To validate the reliability of this model, several tests have been carried out under ambient conditions. The tests results show that the interior temperature error is within 5% between simulated value and experimental data. Also the simulated conduction thermal load gained through cabin panels except bottom panel closely follows the heat conduction measured by HFM-215 which both value fluctuate around 900 W. In addition, detailed analysis on how to reduce the thermal conduction load is put forward in this paper, which shows that cutting down thermal conductivity of envelopes will be the most effective method among thickness, thermal conductivity and special heat capacity of envelopes. Meanwhile, the influences of solar altitude to solar radiation thermal load, vehicle velocity to interior panel temperature, glazing transmissivity to solar radiation thermal load and total thermal load during the process of driving for a whole day have also been analyzed in detail in this paper.